2004
DOI: 10.1111/j.0958-7578.2004.00503.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of processing characteristics of photochemically treated pooled platelets: target requirements for the INTERCEPT Blood System comply with routine use after process optimization

Abstract: To ensure good performance of pathogen inactivation with the INTERCEPT blood system, specific target requirements must be met for platelet dose, volume, plasma content and residual red blood cells (RBCs) prior to photochemical treatment (PCT). A two-arm in vitro study was conducted to compare quality parameters of pooled platelet concentrates (PCs), either treated (test units) or nontreated (control units). PCs meeting European requirements were evaluated with reference to their compliance with INTERCEPT guard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The Intercept system requires product standardization and the use of PAS. An 11% loss of platelets has been reported with the process (Picker et al , 2004). Removal of residual psoralen is required.…”
mentioning
confidence: 97%
“…The Intercept system requires product standardization and the use of PAS. An 11% loss of platelets has been reported with the process (Picker et al , 2004). Removal of residual psoralen is required.…”
mentioning
confidence: 97%
“…Exposure to ultraviolet (UV) radiation in the presence of the synthetic psoralen amotosalen (Intercept System, Cerus Corp., Concord, CA) was the first such technology to be licensed in Europe. Intercept treatment causes increased PLT activation and metabolism in vitro 1,2 and a reduction in the recovery and survival of PLTs after reinfusion to healthy subjects 3 . In two large multicenter clinical studies in stable patients, there was a reduction in PLT count increments after transfusion of amotosalen‐treated PLTs, mainly attributable to their lower dose 4,5 .…”
mentioning
confidence: 99%
“…The manufacturers and users of these devices are interested in having a measurement method sensitive enough to allow determination of device performance and process capability even if the level of cross‐cellular contamination is well below the regulatory recommendations. For example, Picker’s groups reported there are tight limits on the allowable rRBCs in blood products before pathogen inactivation owing to the unique nature of chemical and light treatments 12 . Their study demonstrated a need to modify existing blood product manufacturing processes to meet these tighter requirements that were outside of the range for standard hematology analyzers.…”
mentioning
confidence: 99%
“…For example, Picker's groups reported there are tight limits on the allowable rRBCs in blood products before pathogen inactivation owing to the unique nature of chemical and light treatments. 12 Their study demonstrated a need to modify existing blood product manufacturing processes to meet these tighter requirements that were outside of the range for standard hematology analyzers. To measure the rRBCs, Picker used a flow cytometry (FC) method.…”
mentioning
confidence: 99%